A Model-Based Approach to Analysis and Calibration of Sensor-Based Human Interaction Loops - Parisa Eslambolchilar (International Journal of Mobile Human Computer Interaction, 2010)
The dynamic systems approach to the design of continuous interaction allows designers to use analytical tools such as state-space modeling and Bode diagrams to simulate and analyse the behaviour and stability of sensor-based applications alone and when it is coupled with a manual control model of user behaviour. This approach also helps designers to calibrate and tune the parameters of the sensor-based application before the actual implementation, and in response to user action. In this article the authors introduce some term definitions from manual control theory for the analysis of the continuous aspects of the interaction design and human behaviour. Then we provide a theoretical framework for specification, analysis and calibration of a sensor-based zooming and scrolling application on mobile devices including the user in the interaction loop. It is especially topical and interesting for guiding design of sensor-based applications on mobile devices. We test our framework with a tilt-controlled speed-dependent automatic zooming application on a PDA.